Hydrothermal synthesis of ammonium vanadate [(NH4)2V7O163.6H2O] as a promising zinc-ion cathode: Experimental and theoretical study of its storage. (1st February 2022) - Wang, Zhaojie; Zhang, Jingrui; Wang, Haowei; Wei, Xiaofei; Zhang, Jinbao; Chen, Hongyu; Liu, Siyuan; Wei, Shuxian; Lu, Xiaoqing
Abstract: Aqueous zinc ion batteries (ZIBs) have garnered ongoing scientific and technological interest for safe and eco-friendly energy storage. However, one of the critical challenges is to explore advanced cathode materials for stable and robust zinc ion diffusion. Herein, we demonstrate a simple hydrothermal method to synthesis a new model cathode material of (NH4 )2 V7 O16 3.6H2 O. A systematic experimental and theoretical work is carried out to uncover the advantages of ammonium insertion in V7 O16 layers. Specifically, the ZIB delivers a reversible capacity of 465 and 214 mAh g −1 at current densities of 0.1 and 5.0 A g −1, respectively. Also, it enables an outstanding long-term stability after 1000 cycles at 5A g −1 . Combination of electrochemical investigation and DFT calculations reveals that the unique interlayer structure of (NH4 )2 V7 O16 3.6H2 O endows the favorable Zn 2+ diffusion with suitable adsorption energy and low diffusion energy barrier. This work may pave the way for constructing other high-performance cathode materials for ZIBs and other metal ions batteries.